2018
DOI: 10.23851/mjs.v28i3.542
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect of Acacia Nilotica on Some Gram Positive and Gram Negative Bacteria

Abstract: Acacia nilotica is a plant has an inspiring range of medicinal uses. This plant contributes a number of groups among which are alkaloids, volatile essential oils, phenols and phenolic glycosides, resins, oleosins, steroids, tannins and terpenes, this study aims to: examine the antimicrobial action of ethanolic extraction from fruits and seeds of Acacia nilotica. Hot ethanol extract (48°C) of fruits and seeds obtained from Acacia nilotica, used in minimum bactericidal concentration (MBC), agar diffusion method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…4 In our study ,the phytochemical analysis done on methanol extract and compared with ethanol and aqueous extract of flower Acacia nilotica, results revealed aqueous extract showed the presence of all phytochemical tested whereas methanol and ethanol extract showed the absence of saponin and alkaloid respectively. 13 Ghanghro et al also confirmed presence of alkaloids, flavonoids, tannins, phenols, tannins, saponins and amino acids and they also found heavy metals like nickel (Ni), chromium (Cr), zinc (Zn), cobalt (Co), cadmium (Cd), copper (Cu), manganese (Mn) and iron (Fe). 1 The most perilous metal like Fe (3.97 ppm), Cd (below detection limit) and Mn (0.06 ppm) were detected within the permissible limit in acacia flower.…”
Section: Discussionmentioning
confidence: 94%
“…4 In our study ,the phytochemical analysis done on methanol extract and compared with ethanol and aqueous extract of flower Acacia nilotica, results revealed aqueous extract showed the presence of all phytochemical tested whereas methanol and ethanol extract showed the absence of saponin and alkaloid respectively. 13 Ghanghro et al also confirmed presence of alkaloids, flavonoids, tannins, phenols, tannins, saponins and amino acids and they also found heavy metals like nickel (Ni), chromium (Cr), zinc (Zn), cobalt (Co), cadmium (Cd), copper (Cu), manganese (Mn) and iron (Fe). 1 The most perilous metal like Fe (3.97 ppm), Cd (below detection limit) and Mn (0.06 ppm) were detected within the permissible limit in acacia flower.…”
Section: Discussionmentioning
confidence: 94%